THE EFFECT OF SCAFFOLDING TECHNIQUE ON STUDENTS’ WRITING COMPETENCY - Mahayasa, Gede Wisnu; Suputra, Putu Eka Dambayana; Paramartha, Gede Yudha (Universitas Pendidikan Ganesha, 2021)
ABSTRACTBecause of Covid 19 pandemic, learning is done in online mode by using various online learning platform. This study aims at investigating the effect of scaffolding technique on students’ writing competency in online learning. To run this research, 60 eleventh grade students of SMAN 1 Sukasada in the academic year 2020/2021 were chosen as the samples. This research applied nonequivalent control group design in which there were two groups compared, namely: scaffolding technique and conventional technique. The data of writing competency were collected by using performance test which were then scored by using analytical scoring rubric. The collected data were then analyzed by using independent sample t test. This research shows that there is no significant effect of Scaffolding technique on students’ writing competency with probability value of 0.606 (p>0,05).Keywords: Scaffolding technique, writing competency, skills